AKIBAT HUKUM PERJANJIAN PERKAWINAN BAGI UMAT ISLAM DALAM PERSPEKTIF SYARAT SAHNYA PERJANJIAN - Andi Ibnu Hadi Andi (STAINU Tasikmalaya, 2023)
The marriage agreement is an agreement made by the prospective husband and wife before marriage which regulates the rights and obligations of the spouses in marriage. In the perspective of Western Civil Law, an agreement is binding for those who make an agreement like a law (Facta Sun Servanda) as long as it fulfills the legal requirements of the agreement. Thus, it is necessary to examine more deeply some of the things that are the rights and obligations of husband and wife in marriage ties based on Islamic law, so that the agreement can fulfill the requirements of a valid agreement as stipulated in Article 1320 of the Civil Code. The objective of this research is theoretically to develop Islamic Family Law and Western Civil Law. Practically this research can be used by legal practitioners and the public who will make a marriage agreement for Muslims. This research method is descriptive analysis with normative and empirical juridical approaches. From the results of the research that there is a marriage agreement that is made according to the norms of Islamic law. Based on the legal terms of the agreement, Article 1320 of the Civil Code, the points of agreement on marriage agreements for Muslims that are not in accordance with Islamic marriage law norms are null and void or can be cancelled.